Profitability of Nigerian Deposit Money Banks Listed on NGX and Chief Executive Officer Attributes - Osueke, Chikamso; Olasupo, Sunday fESTUS; Olu-Akinolaa, Fadekemi Ruth; Akanbi, Gloria Oluwamayowa; Otekunrin, Adegbola; Olowoseunre, Deborah Funmilayo; Adigun, Grace Toyin; Doorasamy, Mishelle; Olaosebikan, Johnson Olusola; Imohiosen, Augustine Bamidele (International Journal of Economics and Financial Issues, 2025)
CEO traits are a determining factor for the performance and profitability of deposit money banks, especially in developing economies like Nigeria where leadership trends dictate company success. This study investigates how CEO attributes influence the profitability of Nigerian deposit money banks on the Nigerian Exchange Group (NGX). An ex post facto design was employed with secondary data collected from the annual reports of 20 purposively sampled deposit money banks over the period 2015 to 2023. CEO attributes such as ownership, origin, gender, nationality, and tenure were used as independent variables, whereas return on assets (ROA) served as the profitability measure. Content analysis based on the Integrated Internal Reporting Framework (IIRF) 2021 informed the process of data extraction. Panel regression was applied to explore the relationship between CEO attributes and profitability, with firm size and age controls. The results show that CEO ownership, origin, gender, nationality, and tenure have a significant relationship with bank profitability (p < 0.05), with CEO ownership and tenure having especially strong positive relationships. Firm age also had a negative influence on profitability, which indicates older bank-related problems. The model explained approximately 24.1% of profitability variance (R² = 0.241). The findings identify the strategic CEO characteristics' contribution to enhanced financial performance. To conclude, the study confirms that CEO characteristics significantly influence Nigerian deposit money banks' profitability and offers practical implications for regulators and stakeholders who are interested in improving leadership recruitment and governance for improved bank performance.